Knowledge and Practices on Complementary Feeding among Mothers of Children Aged 6-12 Months in Sissili Province, Burkina Faso - Koffi Apéali Wassiou Agbokou; Ousmane Ouédraogo; Rasmata Dabo; Ella Wendinpuikondo Raketa Compaoré; Donald Ouédraogo; Adama Ouattara; Mouawiyatou Bouraima; Virginio Pietra; Laurencia Toulsoumdé Songré-Ouattara; Mamoudou Hama Dicko (International Journal of Nutrition Sciences)
Background: For prevention of malnutrition of children older than 6 months, Léo Health District of Sissili province in Burkina Faso promoted best complementary feeding practices. So this study evaluated the knowledge and practices of mothers of children aged 6-12 months on complementary feeding in the district.Methods: A cross-sectional study included 163 mothers of children aged 6-12 months aged 6-12 months and coupled at enrollment and after their participation for at least 5 sessions of consultation in relation to ahealthy infant.Results: The proportions of mothers who knew the age of children when complementary foods were administered with a minimum frequency, from 6 to 8 months and 9 to 23 months showed an increase of 5.6%, 16.5% and 2.4%, respectively. Mothers’ knowledge level about the reasons to introduce complementary foods, the names of the three food groups and the ingredients to be added to cereal porridges to enrich them demonstrated a significant improvement. No significant difference was observed between the proportions of mothers with good complementary feeding practices even an increase was noticed. A correlation was visible between the level of knowledge and the complementary feeding practices too.Conclusion: It seems that health services should emphasize the introduction of complementary foods to have a greater impact on optimal complementary feeding practices.